Double major complication in revision spine surgery. A case report - Spalteholz, Matthias; Gulow, Jens (GMS German Plastic, Reconstructive and Aesthetic Surgery – Burn and Hand Surgery, 2020)
Purpose: We present the case of a 69-year-old female patient that suffered double major complication in revision spine surgery. Methods: The patient had to undergo several spine surgeries due to degenerative disorder and adjacent segment disease. After long segment fusion surgery, the patient developed proximal junctional failure with severe thoracic myelopathy. The goal of our revision surgery was to perform a spinal canal clearance in the stenotic thoracic region and to restore the global spine balance by pedicle subtraction osteotomy (PSO) in the fused flat-back lumbar spine. Results: During the PSO closing procedure, we recognized a complete vertebral column dissociation a level above the PSO. This was caused by a tear-off of the intervertebral cage in the prefused lumbar spine. As we were not able to close the osteotomy wedge, we decided to perform a staged anterior column support using an expandable cage. Immediately after the primary posterior surgery, the patient presented a complete paraplegia. Emergency revision did not reveal myelon compression. The anterior spine surgery was done four days later. We transferred the patient to neurological rehab. The patient recovered well, the paraplegia was regressive. The radiological follow-up showed a balanced spine without adjacent segment disease and implant problems. Conclusion: Revision spine surgery is technically demanding. The complication rate is high. The concept of spinopelvic balance is mandatory in long segment fusion surgery to prevent junctional failures, adjacent segment disease, and neurological problems.